Pengaruh Audit Sistem Pengendalian Internal Terhadap Kinerja Pelayanan Instalasi Rawat Inap RS Bhayangkara Bondowoso - Merdekawati, Reni; Syahrinullah, Syahrinullah (Pascasarjana Universitas Muhammadiyah Mamuju, 2025)
This study aims to determine the effect of the internal control system audit on the performance of Inpatient Installation services at Bhayangkara Bondowoso Hospital. This study is a quantitative research, the number of the research population is employees at the inpatient installation of Bhayangkara Bondowoso Hospital. The research sample used a non-probability sampling technique where the entire population became a research sample totaling 29 people. The data collection technique in this study uses a questionnaire that is distributed to a predetermined sample. This study produced the conclusion that the significance value of the T test was 0.000 < 0.05 so that the hypothesis was accepted and the regression coefficient value was obtained with a positive value. So that the audit of the internal control system has a positive and significant effect on service performance. The R Square value is 0.544 which means that the internal control system audit has an effect of 54.4% on service performance, the remaining 45.6% is influenced by other factors that are not examined in this study